Pengaruh Beauty Vlog terhadap Purchase Intention dan Brand Awareness Marina Hand & Body Lotion (Studi pada Pengikut Akun Instagram Alifah Ratu) - Andjarwati, Anik Lestari; Dewi, Lady Arantxa Meilina (Jurnal Minds: Manajemen Ide dan Inspirasi, 2019)
This research was conducted to determine the effect of Vlog on the Purchase Intention of Hand & body lotion and Brand Awareness as an intervening variable. The population in this study were 200 followers of the Alifah Ratu’s Instagram account who had seen Beauty vlog about Marina Hand & body lotion more than once. This type of research uses purposive sampling and quantitative. The technique of collecting data in this study was an online questionnaire and analyzed using path analysis. The results of the research show the beauty of the Vlog is positive and significant to the purchase intention, the beauty of the Vlog is positive and significant to brand awareness. The involvement of the Ratu’s Instagram account, as well as a positive and significant influence between Brand Awareness of the intention to purchase Marina Hand & body lotion.